Kajian Psikososial Pada Tokoh Utama Cerpen Euforia Senja karya Fitriani - Azzam, Abdullah - (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the psychosocial development of the main character in Fitriani’s short story Euforia Senja by applying Erik H. Erikson’s theory of psychosocial development. The focus of this research is on how the main character, Fitriani, experiences psychosocial conflicts and how social interactions and cultural experiences shape her identity and mental health. This research employs a qualitative method with a descriptive-analytical approach, analyzing narratives, dialogues, and character descriptions in the short story. The findings reveal that Fitriani undergoes complex psychosocial conflicts, ranging from trust vs. mistrust, autonomy vs. shame, identity vs. role confusion, to integrity vs. despair. These conflicts illustrate the psychological challenges of adolescence in constructing identity and establishing social relations. The results highlight the relevance of Erikson’s theory in understanding character development in literature while also emphasizing the role of short stories as a reflective medium for exploring adolescent psychological experiences.